A Study on the Social Sustainability of European Tax Systems - Ioana Laura TIBULCA (Communications of International Proceedings, 2021)
The quality of European tax systems has been the focus of political and economics debates for some time. However, aspects regarding the sustainability of fiscal systems do not seem to be high on the list of considered issues. Though many international institutions (OECD, IMF, European Commission) publish an ever-increasing number of indicators which could be used to assess the sustainability of tax systems there is still no widely-acknowledged methodology based on which to decide whether a tax system is sustainable or not. The current study aims to assess the social sustainability of the tax systems of the 27 member states of the EU. This is achieved using the scoring method. Five main objectives that a socially sustainable tax system should help achieve are taken into account. Each tax system is scored on how well it has managed to achieve each objective over the last five years based on values of indicators used to assess each of the goals. An overall score is then determined based on which the social sustainability of the European tax systems can be evaluated. The research results show that 25 EU tax systems are currently socially sustainable.
Keywords: Tax Sustainability; Social Sustainability; Taxation; Income Equality; Gender Gap; Social Inclusion; Tax Moral; Tax Governance.